O impacto da controladoria no tempo de julgamento dos processos disciplinares dos policiais militares do Ceará - Silva, Francinilson Mota da (2013)
The present study tries to expose a statistical analysis of the data collected from the Comptroller General of Discipline relating to disciplinary procedures applied to military police. In this sense, aims to qualitatively evaluate the statistical results obtained. The work developed correição is critical to the performance of military police, considering, discouraging illicit acts by security agents and ensure a welcoming society and security against misconduct of security agents. In our study object the best option was a regression model censored tobit model that was the best fit to the study of variables collected. In the end it describes a qualitative analysis of the results for the variables found.